Ins and Outs of Plagiarism in Academia: Reconnoitring Concepts, Causes, and Consequences - Neupane, Nabaraj (Janapriya Journal of Interdisciplinary Studies, 2023)
For developing fair intellectual practices, one requires paving the path of academic integrity. However, authors have been violating those norms knowingly or unknowingly. They are doing so for some reasons such as academic promotion, public fame, and dignity without hard work, to mention a few. Therefore, plagiarism is rocking the academia and it is high time to prevent it. The first step to prevent this immoral practice is to make the writers aware of its notions, causes, consequences, and ways to avoid it. These are the main aims of this article. Further, this article aims to highlight state-of-the-art and desiderata of the plagiarists’ practices, whose penalties are unavoidable. Employing a review and analysis of a few cases of history, this article draws an inference that writers should follow ethical/legal practices to let intellectual integrity and fairness prosper in the field of academia.